2020
DOI: 10.1002/jcla.23494
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of methicillin‐susceptible Staphylococcus aureus clinical isolates: High prevalence of multidrug‐resistant ST239 with strong biofilm‐production ability

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
(202 reference statements)
0
5
0
Order By: Relevance
“…Notably, all ST239 MRSA isolates harbored cna in contrast to the ST239 MSSA isolates; however, cna was also found in MSSA isolates such as ST1, ST96, and ST188. In a previous study, Zamani et al [33] reported that ST239 MRSA clinical isolates collected between 2018 and 2019 carried cna, while ST239 MSSA isolates from the same institution reported by Goudarzi et al [34] contained no cna gene. However, Zamani et al reported that all ST239 MRSA clinical isolates carried clfA, clfB, fnbA, and fnbB, which differed from our results where ST239 MRSA isolates harbored eno, clfA, clfB, and fib.…”
Section: Discussionmentioning
confidence: 95%
“…Notably, all ST239 MRSA isolates harbored cna in contrast to the ST239 MSSA isolates; however, cna was also found in MSSA isolates such as ST1, ST96, and ST188. In a previous study, Zamani et al [33] reported that ST239 MRSA clinical isolates collected between 2018 and 2019 carried cna, while ST239 MSSA isolates from the same institution reported by Goudarzi et al [34] contained no cna gene. However, Zamani et al reported that all ST239 MRSA clinical isolates carried clfA, clfB, fnbA, and fnbB, which differed from our results where ST239 MRSA isolates harbored eno, clfA, clfB, and fib.…”
Section: Discussionmentioning
confidence: 95%
“…The CC8 clone is described to be a prevalent iMLSB phenotype MRSA in Iran (11). In addition, Goudarzi et al reported that isolates with iMLSB phenotype were observed in CC88/ST239 (13.3%), CC/ST22 (4%), and CC/ST30 (4%) clonal lineages (12).…”
Section: Discussionmentioning
confidence: 99%
“…After the genomic DNA extraction using the phenol-chloroform technique, isolates were screened for the existence of the toxin genes, including pvl, eta, etb, and tst, by PCR (10,12). The mupA, fusA, mecC, and mecA genes were detected by PCR as described elsewhere (4).…”
Section: Detection Of Resistance and Toxin-encoding Determinantsmentioning
confidence: 99%
“…MSSA-ST30 is an ancestral strain of an epidemic MRSA clone which evolved into MSSA, and is also known as the Southwest Pacific clone [ 60 ]. ST30 is an international successful clone since it has been found in Australia, Europe and Asia [ 61 ]. This lineage is primarily associated with humans, but it has been also found among animals and in the environment [ 55 , 62 ].…”
Section: Discussionmentioning
confidence: 99%